Influence of aluminum addition on the laser powder bed fusion of copper-aluminum mixtures - Nada Kraiem; Loic Constantin; Aofei Mao; Fei Wang; Bai Cui; Jean-François Silvain; Yong Feng Lu (Additive Manufacturing Letters, 2022)
The high optical reflectivity of copper (Cu) in the near infrared (NIR) domain and its elevated heat dissipation make Cu a challenging metal for laser powder bed fusion (LPBF), even with high energy densities (EDs). In this study, we demonstrated that adding aluminum (Al) powder by as little as 0.75, 1.5, and 3 wt.% substantially enhances Cu processability, leading to denser (up to 98%) and smoother (Ra = 3.3 μm) Cu-Al parts as compared to 95% and 18 μm, respectively, for the parts printed using pure Cu. In addition, this method reduces the ED required by a factor of two for the additive manufacturing of the Cu-based parts while maintaining a significant heat dissipation. These improvements are achieved due to the coexistence of solid Cu particles with liquid Al at the vicinity of the molten pool, accomodating the predensification of the powder mixture. The development of the semi-liquid 3D printing approach opens up a new path to easily manufacture materials difficult to be printed for broadening their applications.